Preparation method of lithium ion battery negative electrode slurry

By adopting the composite system and optimization process of CMC, PAA and SBR in the preparation of negative electrode slurry of lithium-ion batteries, the problems of uneven particle distribution, poor adhesion and poor low-temperature performance in the prior art are solved, and the performance of lithium-ion batteries is significantly improved.

CN119581555APending Publication Date: 2025-03-07JIANGSU WANLI NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411694463.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode slurry preparation methods have problems such as uneven particle distribution, poor adhesion, large rebound of the electrode sheet and poor low-temperature performance, which limits the further improvement of the performance of lithium-ion batteries.

Method used

A composite system composed of CMC, PAA and SBR is adopted to optimize the ratio and preparation process parameters between each component to form a uniformly dispersed mixed powder, and the final lithium-ion battery negative electrode slurry is obtained through vacuum defoaming and precision filtration.

Benefits of technology

The dispersion uniformity and stability of the active material in the negative electrode slurry is significantly improved, the coating performance and low-temperature performance of the slurry are improved, the rebound phenomenon of the electrode sheet is reduced, and the uniformity and density of the negative electrode layer of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151780820000071
    Figure BDA0005151780820000071
Patent Text Reader

Abstract

The invention discloses a preparation method of lithium ion battery negative electrode slurry, which is characterized by comprising the following steps: step 1, sequentially adding 0.5-1 part by weight of CMC dry powder, 0.5-1.2 parts by weight of a conductive agent and 95-97.5 parts by weight of an active substance into a stirring kettle, enabling the stirring kettle to rotate at 400-600 rpm and revolve at 20-30 rpm, and stirring for 20-30 minutes, so that each component is fully and uniformly dispersed to form required mixed powder; step 2, deionized water is added into the mixed powder obtained in the step 1 for kneading, the rotation speed of a stirring kettle is 0 rpm, the revolution speed of the stirring kettle is 20-30 rpm, and the kneading time is 30-60 min; 3, adding 1-2.5 parts by weight of PAA, dispersing at a high speed, and uniformly stirring; the rotation speed of the stirring kettle is 1500-2000 rpm, and the revolution speed is 25-30 rpm. According to the preparation method of the lithium ion battery negative electrode slurry disclosed by the invention, the viscosity characteristic of the slurry is reasonably regulated and controlled, so that the slurry is ensured to have excellent coating performance, and precipitation in the standing process can be avoided, thereby remarkably improving the uniformity and density of a battery negative electrode layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing negative electrode slurry of lithium ion batteries. Background Art

[0002] With the vigorous development of the new energy industry, lithium-ion batteries, as important energy storage and conversion devices, are crucial to the development of electric vehicles, energy storage systems and other fields. As a key component of lithium-ion batteries, the quality of negative electrode slurry directly affects the energy density, cycle life and safety of the battery.

[0003] The main system of aqueous negative electrode slurry for lithium-ion batteries is CMC+SBR. SBR is used as an adhesive in the SBR+CMC negative electrode system. Due to the low viscosity of the SBR aqueous solution, it cannot suspend the slurry, and CMC must be added to the slurry as a thickener. However, the SBR+CMC system is prone to roller sticking during processing, resulting in negative electrode powder loss and large electrode rebound. SBR will also cause the internal resistance of the battery to increase at low temperatures.

[0004] Existing methods for preparing negative electrode slurries for lithium-ion batteries often suffer from uneven particle distribution, poor adhesion, large electrode rebound, and poor low-temperature performance, which limits further improvement in the performance of lithium-ion batteries. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing a negative electrode slurry for a lithium-ion battery, the purpose of which is to solve the problems of uneven particle distribution, poor adhesion, large electrode rebound, poor low-temperature performance, and limiting the further improvement of lithium-ion battery performance.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is: a method for preparing a negative electrode slurry for a lithium ion battery, comprising the following steps:

[0007] Step 1: 0.5-1 parts by weight of CMC dry powder, 0.5-1.2 parts by weight of conductive agent and 95-97.5 parts by weight of active material are sequentially added into a stirring kettle, the stirring kettle rotates at 400-600 rpm, revolves at 20-30 rpm, and stirs for 20-30 minutes to make each component fully and evenly dispersed to form the required mixed powder;

[0008] Step 2: Add deionized water to the mixed powder obtained in step 1 and knead it. The stirring kettle rotates at 0 rpm and orbits at 20-30 rpm for 30-60 min.

[0009] Step 3: Add 1-2.5 parts by weight of PAA, disperse at high speed, and stir evenly; rotate the stirring kettle at 1500-2000 rpm, revolve at 25-30 rpm, and stir for 60-90 minutes;

[0010] Step 4: Add deionized water and disperse and stir again to ensure the viscosity reaches 4000-7000mpas;

[0011] Step 5: Add 0.5 to 1 parts by weight of SBR and disperse at a low speed to meet the requirements of the subsequent coating process;

[0012] Step six: Place the slurry in a vacuum environment for defoaming treatment, and remove impurities through a precision filter to obtain the final lithium-ion battery negative electrode slurry.

[0013] Furthermore, the lithium-ion battery negative electrode slurry, except for ionized water, has the following raw material components by weight: 0.5-1 part of CMC, 0.5-1 part of conductive agent, 95-97.5 parts of negative electrode active material, 1-2.5 parts of PAA, and 0.5-1 part of SBR.

[0014] Furthermore, the negative electrode active material described in step one is natural graphite, hard carbon, and mesophase carbon microspheres.

[0015] Furthermore, the particle size D50 of the artificial graphite is 10 to 30 μm, the specific surface area is 1.0 to 2.0 m2 / g, and the tap density is 1 to 1.25 g / cm3.

[0016] Furthermore, the solid content of the kneading in the step 2 is 66% to 69%.

[0017] Furthermore, the rotation speed of the low-speed dispersion in step 5 is 800-1000 rpm, and the dispersion time is 20-30 min.

[0018] Furthermore, the vacuum pressure of the vacuum defoaming in step six is ​​-0.085MPa to -0.095MPa, the solid content of the slurry is 49% to 52%, and the viscosity is 3000 to 6000mpas.

[0019] Furthermore, the high-speed dispersion time in step 2 and step 3 is 90 to 150 minutes.

[0020] The beneficial effects of the present invention are:

[0021] The present invention discloses a method for preparing a negative electrode slurry for a lithium-ion battery. By adopting a composite system composed of CMC, PAA and SBR, and by carefully optimizing the ratio between the components and the preparation process parameters, the method significantly improves the dispersion uniformity and stability of the active material in the negative electrode slurry, and effectively inhibits the agglomeration tendency of the active material. In the preparation process, the present invention reasonably regulates the viscosity characteristics of the slurry to ensure that the slurry has both excellent coating performance and can avoid precipitation during the standing process, thereby significantly improving the uniformity and density of the negative electrode layer of the battery. In addition, the prepared negative electrode slurry exhibits good electrical conductivity and low internal resistance, effectively enhancing the bonding strength between the negative electrode slurry and the current collector, and significantly reducing the rebound phenomenon of the pole piece during the charge and discharge process, further improving the low temperature performance of the battery.

[0022] The invention discloses a method for preparing a negative electrode slurry for a lithium-ion battery. In terms of raw material selection, the invention fully considers environmental protection and economy, and adopts widely available and cost-effective raw materials, which is not only conducive to reducing production costs, but also provides strong support for large-scale industrial production. The prepared negative electrode slurry for a lithium-ion battery is suitable for the manufacture of high-performance lithium-ion batteries, and exhibits excellent cycle stability and safety.

[0023] The invention discloses a method for preparing negative electrode slurry for lithium ion batteries. The method has simple process, low cost and is easy to realize large-scale industrial production, which has positive significance for promoting the sustainable development of the lithium ion battery industry. DETAILED DESCRIPTION

[0024] In order to make the contents of the present invention more clearly understood, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.

[0025] A method for preparing a negative electrode slurry for a lithium ion battery comprises the following steps:

[0026] Step 1: 0.5-1 parts by weight of CMC dry powder, 0.5-1.2 parts by weight of conductive agent and 95-97.5 parts by weight of active material are sequentially added into a stirring kettle, the stirring kettle rotates at 400-600 rpm, revolves at 20-30 rpm, and stirs for 20-30 minutes to make each component fully and evenly dispersed to form the required mixed powder;

[0027] Step 2: Add deionized water to the mixed powder obtained in step 1 and knead it. The stirring kettle rotates at 0 rpm and orbits at 20-30 rpm for 30-60 min.

[0028] Step 3: Add 1-2.5 parts by weight of PAA, disperse at high speed, and stir evenly; rotate the stirring kettle at 1500-2000 rpm, revolve at 25-30 rpm, and stir for 60-90 minutes;

[0029] Step 4: Add deionized water and disperse and stir again to ensure the viscosity reaches 4000-7000mpas;

[0030] Step 5: Add 0.5 to 1 parts by weight of SBR and disperse at a low speed to meet the requirements of the subsequent coating process;

[0031] Step six: Place the slurry in a vacuum environment for defoaming treatment, and remove impurities through a precision filter to obtain the final lithium-ion battery negative electrode slurry.

[0032] Deionized water is removed from the negative electrode slurry of a lithium-ion battery, and the raw material components are as follows by weight: 0.5 to 1 part of CMC, 0.5 to 1 part of a conductive agent, 95 to 97.5 parts of a negative electrode active material, 1 to 2.5 parts of PAA, and 0.5 to 1 part of SBR.

[0033] The negative electrode active materials in step one include natural graphite, hard carbon, and mesophase carbon microspheres.

[0034] The particle size D50 of artificial graphite is 10-30 μm, the specific surface area is 1.0-2.0 m2 / g, and the tap density is 1-1.25 g / cm3.

[0035] The solid content of kneading in step 2 is 66% to 69%.

[0036] In step 5, the rotation speed of the low-speed dispersion is 800-1000 rpm, and the dispersion time is 20-30 min.

[0037] The vacuum pressure of the vacuum defoaming in step six is ​​-0.085MPa to -0.095MPa, the solid content of the slurry is 49% to 52%, and the viscosity is 3000 to 6000mpas.

[0038] The high-speed dispersion time in step 2 and step 3 is 90 to 150 minutes.

[0039] Example 1

[0040] Step 1: Add 0.5 parts by weight of CMC dry powder, 0.8 parts by weight of conductive agent and 95.7 parts by weight of active material into a stirring tank, rotate the stirring tank at 600 rpm and orbit at 25 rpm, and stir for 20 minutes to obtain a mixed powder;

[0041] Step 2: Add deionized water to the mixed powder obtained in step 1 and knead it. The stirring kettle rotates at 0 rpm and revolves at 25 rpm. The kneading time is 40 minutes and the kneading solid content is 68%;

[0042] Step 3: Add 2 parts by weight of PAA, disperse at high speed, and stir evenly; rotate the stirring kettle at 1500 rpm and 25 rpm, and stir for 60 minutes;

[0043] Step 4: Use deionized water to adjust the viscosity to 6560mpas;

[0044] Step 5: Add 1 part by weight of SBR and disperse at low speed;

[0045] Step 6: Vacuum defoaming, the vacuum degree is -0.09MPa, and filter to obtain a lithium ion battery negative electrode slurry with a solid content of 50% and a viscosity of 5500mpas;

[0046] The change in solid content of the upper and lower layers of the slurry after being left for 48 hours was measured, and the negative electrode slurry was used to prepare the negative electrode sheet. The peel strength of the sheet was tested and the rebound rate of the sheet after full charge was calculated.

[0047] Example 2

[0048] Step 1: Add 0.5 parts by weight of CMC dry powder, 1 part by weight of conductive agent and 95.2 parts by weight of active material into a stirring tank, rotate the stirring tank at 800 rpm and orbit at 25 rpm, and stir for 30 minutes to obtain a mixed powder;

[0049] Step 2: Add deionized water to the mixed powder obtained in step 1 and knead it. The stirring kettle rotates at 0 rpm and revolves at 30 rpm. The kneading time is 30 min and the kneading solid content is 67%;

[0050] Step 3: Add 2.5 parts by weight of PAA, disperse at high speed, and stir evenly; rotate the stirring kettle at 1800 rpm and 25 rpm, and stir for 60 minutes;

[0051] Step 4: Use deionized water to adjust the viscosity to 6000mpas;

[0052] Step 5: Add 0.8 parts by weight of SBR and disperse at a low speed;

[0053] Step 6: Vacuum defoaming, the vacuum degree is -0.095MPa, filter, and obtain a solid content of 50.6%.

[0054] Lithium-ion battery negative electrode slurry with a viscosity of 5000mpas;

[0055] The change in solid content of the upper and lower layers of the slurry after being left for 48 hours was measured, and the negative electrode slurry was used to prepare the negative electrode sheet. The peel strength of the sheet was tested and the rebound rate of the sheet after full charge was calculated.

[0056] Example 3

[0057] Step 1: Add 0.7 parts by weight of CMC dry powder, 0.7 parts by weight of conductive agent and 95.8 parts by weight of active material into a stirring tank, rotate the stirring tank at 1000 rpm, revolve at 30 rpm, and stir for 20 minutes to obtain a mixed powder;

[0058] Step 2: Add deionized water to the mixed powder obtained in step 1 and knead it. The stirring kettle rotates at 0 rpm and revolves at 30 rpm. The kneading time is 45 minutes and the kneading solid content is 68%;

[0059] Step 3: Add 1.8 parts by weight of PAA, disperse at high speed, and stir evenly; rotate the stirring kettle at 2000 rpm, revolve at 30 rpm, and stir for 60 minutes;

[0060] Step 4: Use deionized water to adjust the viscosity to 5800mpas;

[0061] Step 5: Add 1 part by weight of SBR and disperse at low speed;

[0062] Step 6: Vacuum defoaming, the vacuum degree is -0.085MPa, and filter to obtain a lithium ion battery negative electrode slurry with a solid content of 52% and a viscosity of 4500mpas;

[0063] The change in solid content of the upper and lower layers of the slurry after being left for 48 hours was measured, and the negative electrode slurry was used to prepare the negative electrode sheet. The peel strength of the sheet was tested and the rebound rate of the sheet after full charge was calculated.

[0064] Comparative Example 1

[0065] Step 1: Add 1.5 parts by weight of CMC dry powder, 1 part by weight of conductive agent and 95.2 parts by weight of active material into a stirring tank, rotate the stirring tank at 1000 rpm and orbit at 30 rpm, and stir for 20 minutes to obtain a mixed powder;

[0066] Step 2: Add deionized water to the mixed powder obtained in step 1 and knead it. The stirring kettle rotates at 0 rpm and revolves at 30 rpm. The kneading time is 45 minutes and the kneading solid content is 68%;

[0067] Step 3: Use deionized water to adjust the viscosity to 5800mpas;

[0068] Step 4: Add 2.3 parts by weight of SBR and disperse at low speed for 30 minutes

[0069] Step 5: vacuum defoaming, the vacuum degree is -0.085MPa, and filtering is performed to obtain a lithium ion battery negative electrode slurry with a solid content of 48% and a viscosity of 3800mpas;

[0070] The change in solid content of the upper and lower layers of the slurry after being left for 48 hours was measured, and the negative electrode slurry was used to prepare the negative electrode sheet. The peel strength of the sheet was tested and the rebound rate of the sheet after full charge was calculated.

[0071] The solid content of the slurries of Examples 1, 2, 3 and the comparative example was changed and the negative electrode sheets were prepared with the negative electrode slurries for testing. The results are shown in Table 1:

[0072]

[0073] From the data in Table 1, it can be seen that compared with the CMC+SBR system, the difference in 48h solid content (upper layer / lower layer) of the CMC+SBR+PAA system is smaller, indicating that the stability of the slurry is better. The peel strength represents the adhesion of the electrode. The greater the peel strength, the greater the adhesion of the electrode.

[0074] The pole piece prepared by the method of the present invention has a large peel strength, indicating better adhesion, and the data in the table show that the pole piece rebound rate is 5% lower.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode slurry for a lithium ion battery, characterized in that: The following steps are involved: Step 1: 0.5-1 parts by weight of CMC dry powder, 0.5-1.2 parts by weight of conductive agent and 95-97.5 parts by weight of active material are sequentially added into a stirring kettle, the stirring kettle rotates at 400-600 rpm, revolves at 20-30 rpm, and stirs for 20-30 minutes to make each component fully and evenly dispersed to form the required mixed powder; Step 2: Add deionized water to the mixed powder obtained in step 1 and knead it. The stirring kettle rotates at 0 rpm and orbits at 20-30 rpm for 30-60 min. Step 3: Add 1-2.5 parts by weight of PAA, disperse at high speed, and stir evenly; rotate the stirring kettle at 1500-2000 rpm, revolve at 25-30 rpm, and stir for 60-90 minutes; Step 4: Add deionized water and disperse and stir again to ensure the viscosity reaches 4000-7000mpas; Step 5: Add 0.5 to 1 parts by weight of SBR and disperse at a low speed to meet the requirements of the subsequent coating process; Step six: Place the slurry in a vacuum environment for defoaming treatment, and remove impurities through a precision filter to obtain the final lithium-ion battery negative electrode slurry.

2. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The lithium ion battery negative electrode slurry, except for ionized water, has the following raw material components by weight: 0.5-1 part of CMC, 0.5-1 part of conductive agent, 95-97.5 parts of negative electrode active material, 1-2.5 parts of PAA, and 0.5-1 part of SBR.

3. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The negative electrode active materials described in step 1 are natural graphite, hard carbon, and mesophase carbon microspheres.

4. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The particle size D50 of the artificial graphite is 10-30 μm, the specific surface area is 1.0-2.0 m2 / g, and the tap density is 1-1.25 g / cm3.

5. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The solid content of the kneading in the step 2 is 66% to 69%.

6. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The rotation speed of the low-speed dispersion in the step 5 is 800-1000 rpm, and the dispersion time is 20-30 min.

7. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The vacuum pressure of the vacuum defoaming in step 6 is -0.085MPa to -0.095MPa, the solid content of the slurry is 49% to 52%, and the viscosity is 3000 to 6000mpas.

8. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The high-speed dispersion time in step 2 and step 3 is 90 to 150 minutes.

Citation Information

Cited By

  • Negative electrode slurry, negative electrode plate, preparation method of negative electrode slurry and negative electrode plate, and battery

    CN120709373A